2011
DOI: 10.1371/journal.pone.0017579
|View full text |Cite
|
Sign up to set email alerts
|

Viral Etiology of Influenza-Like Illnesses in Antananarivo, Madagascar, July 2008 to June 2009

Abstract: BackgroundIn Madagascar, despite an influenza surveillance established since 1978, little is known about the etiology and prevalence of viruses other than influenza causing influenza-like illnesses (ILIs).Methodology/Principal FindingsFrom July 2008 to June 2009, we collected respiratory specimens from patients who presented ILIs symptoms in public and private clinics in Antananarivo (the capital city of Madagascar). ILIs were defined as body temperature ≥38°C and cough and at least two of the following sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
96
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(133 citation statements)
references
References 26 publications
33
96
4
Order By: Relevance
“…This could be either because of differences in the health‐seeking behaviours of men and women or because gender is a risk factor for respiratory virus infection. Some previous studies have also reported higher positivity rates in males, 15,35,36 while others have reported higher rates in females, 12,26,37–39 but only in our study are gender differences statistically significant. A chi‐square analysis comparing the gender of included and excluded patients found no statistically significant gender difference between the two groups (χ 2 = 1·14, P = 0·29), ruling out any possibility that this finding could have been due to recruitment or diagnostic bias.…”
Section: Discussioncontrasting
confidence: 82%
“…This could be either because of differences in the health‐seeking behaviours of men and women or because gender is a risk factor for respiratory virus infection. Some previous studies have also reported higher positivity rates in males, 15,35,36 while others have reported higher rates in females, 12,26,37–39 but only in our study are gender differences statistically significant. A chi‐square analysis comparing the gender of included and excluded patients found no statistically significant gender difference between the two groups (χ 2 = 1·14, P = 0·29), ruling out any possibility that this finding could have been due to recruitment or diagnostic bias.…”
Section: Discussioncontrasting
confidence: 82%
“…However, the study did not consider bacterial pathogens. On the other hand, the studies of respiratory infections among children of Zambia and Madagascar reported the detection rates of respiratory pathogens in 76.8% and 74.6% specimens, respectively, and these studies focused on the detection of both viral and atypical bacterial pathogens [20, 21]. A similar study conducted in China demonstrated 67.5% overall pathogen detection rate [22].…”
Section: Discussionmentioning
confidence: 99%
“…Many putative mechanisms have been put forward, but a unifying theory accounting for the diversity of seasonal patterns observed globally remains elusive . A better understanding of influenza seasonality is important to help tailor surveillance strategies and optimize the local timing of influenza vaccination, especially in developing country settings where influenza disease burden is becoming increasingly recognized …”
Section: Introductionmentioning
confidence: 99%